Emerging cardiovascular toxicity associated with CDK4/6 inhibitors: real-world insights from the FDA adverse event reporting system - Liu, Wensheng; Gao, Feifei; Song, Xue; Chen, Hao; She, Youjun; Liu, Jiyong; Du, Qiong (Frontiers in Pharmacology, 2025)
BackgroundDespite the unprecedented advancement of cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6i) in the treatment paradigm for hormone-dependent breast cancer, reports of cardiovascular adverse events (CVAEs) in both pivotal trials and real-world settings have garnered concerns.Objectiveswe aim to profile the incidence, clinical characteristics and risk factors of CVAEs associated CDK4/6i to provide a vigilant reference for cancer management.MethodsThe global disproportionality study was conducted by utilizing safety reports submitted to the FDA adverse event reporting system (FAERS) during the period from January 2015 to September 2024. Reporting odds ratio (ROR) was employed to identify and evaluate emerging CVAEs related to CDK4/6i. Multivariable logistic regression analysis was utilized to explore factors associated with CVAEs following CDK4/6i treatment. Parametric and cumulative distribution was used for the reported time-to-onset analysis.ResultsA total of 4,709 reports of CVAEs were identified with CDK4/6i, of which 4264 (90.5%) were classified as serious and 12.0% were fatal situation. The median onset time of CVAEs with CDK4/6i was 102 days (interquartile range [IQR], 25-374 days). Disproportionality analysis revealed that Abemaciclib was significantly increased signal of venous thromboembolism (ROR = 2.57 [2.24-2.96]), whereas cardiac arrhythmia (ROR = 2.51 [2.13-2.96]) and torsade de pointes/QT prolongation (ROR = 5.7 [5-6.5]) were showed significantly disproportionate for ribociclib. Meanwhile, cerebrovascular accident and thrombosis were showed significant associated with Abemaciclib ribociclib or palbociclib treatment. Some emerging potential CVAEs, such as myocardial infarction and pulmonary edema, were found to be significantly associated with ribociclib and palbociclib. Additionally, age exceeding 65 years and types of CDK4/6i were significant risk factors for the incidence of CDK4/6i-related CVAEs.ConclusionCVAEs might occur with a greater frequency in the context of CDK4/6i than had been previously acknowledged. Our study provide an overview of the incidence, characteristics and risk factors of CDK4/6i-related CVAEs, and also uncovered potential CVAEs that were not identified in the clinical trials.